PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PT POS INDONESIA CABANG CIPUTAT TANGERANG SELATAN - Widayati Pratiwi, Zhera; Purnama, Aan (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of physical work environment and work motivation on employee performance at PT Pos Indonesia Ciputat Branch. This study uses quantitative methods with data collection techniques through distributing questionnaires and library/literature data. The population in this study were 139 employees. The sample used was 58 employees using the Slovin technique. The data analysis used is validity test analysis, reliability test, classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient test, determination coefficient test and hypothesis testing. The results showed that the Physical Work Environment has a significant effect on Employee Performance, it can be seen from the results of the t test obtained a tcount value of 3.323> t table 1.673 and a significant 0.002 <0.05. Work Motivation has a significant effect on Employee Performance, it can be seen from the results of the t test obtained the t value of 5.784> t table 1.673 and significant 0.000 <0.05. Simultaneously, the Physical Work Environment and Work Motivation have a positive and significant effect, this can be proven by the results of the F test which shows that Fcount>Ftabel is (66.842>3.16) and significant 0.05 (0.000 <0.05).